The description logic handbook : theory, implementation, and applications - Baader, Franz (Cambridge University Press, 2003)
The Description Logic Handbook covers all aspects of the research in the field of knowledge representation. Written by some of the most prominent researchers in the field, and covering the basic technical material and implementational aspects, it is both a unique reference and a self-study guide.